The Main Conditions of Forming Ukrainian Diaspora in the USA - Nych, Oksana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The historical and political aspects of the Ukrainian Diaspora forming are depicted in the article. The main attention is paid to the four waves of the Ukrainian immigration. The author analyzes the reasons of Ukrainian migration and shows the historical and political conditions of it formation